Induksi Tunas pada Kotiledon dan Hipokotil Tanaman Jarak Pagar (Jatropha curcas L.) melalui Organogenesis Tak Langsung - Iswari S Dewi; Anggi Nindita; Bambang S. Purwoko; Darda Efendi (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
Propagation through tissue culture of plantspecies with rich secondary metabolites such as Jatrophacurcas L. is difficult to obtain. However, once established, itcan be used as one of the alternatives to supply uniformpropagules. The effects of auxin and cytokinin on theregulation of de novo woody plants shoot development havebeen studied through shoot induction, differentiation anddevelopment. The objective of this research was to identifyexplant and suitable culture media for in vitro shoot inductionthrough indirect organogenesis. Factorial experimentwas arranged in a completely randomized design, replicated20 times. The first factor was explants, i.e. cotyledons andhypocotyls. The second factor was MS media containingcombination of plant growth regulator IAA (0, 0.05, and 0.1mg/l) and BAP (0, 1.0, 2.0, 3.0 mg/l). The results of theexperiment showed that the fastest callus initiation wasachieved by MS + IAA 0.1 mg/l, i.e. 9.5 days after explantswere cultured. Shoots with leaves can be induced from bothcotyledons and hypocotyls. However, hypocotyls gave moreshoots and leaves than cotyledons when cultured in MS +IAA 0.1 mg/l + BAP 3.0 mg/l. Shoots obtain from hypocotylsand cotyledons were successfully rooted in MS mediumwithout any growth regulator.